Pemurnian alfa-selulosa dari baglog bekas jamur tiram putih (Pleurotus ostreatus) menggunakan NaOH dan hidrolisis sulfat (Purification of alpha-cellulose from ex-baglog of white oyster mushroom (Pleurotus ostreatus) using NaOH and sulfate hydrolysis) - Hyakansa HANIF; TRI - PANJI; Firda DIMAWARNITA; I Made ARTIKA (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2019)
Oil Palm Empty Fruit Bunches (OPEFB) are the largest cellulose waste produced by oil palm plantations. Each processing of one ton of Fresh Fruit Bunch (FFB) will produce OPEFB as much as 22-23% or 220-230 kg. OPEFB waste has not been utilized optimally by most palm oil mills and communities. It was reported that OPEFB contains 32.57% cellulose, 27.70% hemicellulose, and 26.49% lignin. The purity of cellulose component in OPEFB can be increased by delignification and hydrolysis of OPEFB. This research aims to produce alpha-cellulose from OPEFB with the highest purity level. The stages of the process include biologically delignification using white oyster mushroom (Pleurotus ostreatus), chemical delignification using 17,5% NaOH solution, and combination of treatment using solution of 17,5% NaOH and hydrolysis using 10% H2SO4solution. The analysis was carried out using the Fourier Transform Infrared Spectroscopy (FTIR). The best result of alpha-cellulose purity was by the treatment of delignified NaOH baglog resulting in 97.43% alpha-cellulose content, 4.47% pentosan hemicellulose level, and undetectable lignin levels.The results of FT-IR spectrum from alpha-cellulose obtained from OPEFB has shown functional groups contained in alpha-cellulose polymers including O-H groups at wave number 3289 cm-1, C-H groups at wave number 2901 cm-1, and functional groups C-O at wave number 1372 cm-1.[Key words: hydrolysis, FT-IR, mushroom, bleaching, waste] Abstrak Tandan kosong kelapa sawit (TKKS) adalah limbah terbesar yang dihasilkan oleh perkebunan kelapa sawit. Setiap pengolahan satu ton tandan buah segar (TBS) akan dihasilkan TKKS sebanyak 22-23% atau 220-230 kg. Limbah TKKS belum dimanfaatkan secara optimaloleh sebagian besar pabrik kelapa sawit (PKS) dan masyarakat. Dari hasil analisis kimiakomposisi selulosa, hemiselulosa, dan lignin pada TKKSsecara berturut-turut ialah ; 32,57%, 27,70%, 26,49%. Kandungan komponen selulosa dalam TKKSdapat ditingkatkan kemurniannya dengan cara delignifikasi dan hidrolisis. Penelitian ini bertujuan pemurnian alfa–selulosa dari TKKS dengan tingkat kemurnian tertinggi.Tahapan pembuatan alfa-selulosameliputi delignifikasi secara biologis menggunakan jamur tiramputih(Pleurotus ostreatus), delignifikasi secara kimia menggunakan larutan NaOH 17,5%, dan kombinasi perlakuan menggunakan NaOH 17,5% dan larutanH2SO410%. Analisis dilakukan menggunakanFourier Transform Infrared Spektroscopy (FT-IR). Hasil pemurnian alfa-selulosa terbaik ialah melalui sisa baglog terdelignifikasi NaOH menghasilkan kadar alfa-selulosa 97.43%, kadar pentosan hemiselulosa 4.47%, serta kadar lignin tidak terdeteksi. Hasil spektrumFT-IR darialfa–selulosayang diperoleh dari TKKStelahmenunjukkan gugus-gugus fungsi yangterdapat di dalam polimeralfa–selulosadiantaranyagugus O-H pada bilangan gelombang 3289 cm-1, gugus C-H pada bilangangelombang2901cm-1, dan gugus fungsi C-O pada bilangan gelombang 1372 cm-1. [Kata kunci: hidrolisis, FT-IR, jamur, pemutihan, limbah]